Population inversion in monolayer and bilayer graphene. (2nd April 2015) - Gierz, Isabella; Mitrano, Matteo; Petersen, Jesse C; Cacho, Cephise; Edmond Turcu, I C; Springate, Emma; Stöhr, Alexander; Köhler, Axel; Starke, Ulrich; Cavalleri, Andrea
Abstract: The recent demonstration of saturable absorption and negative optical conductivity in the Terahertz range in graphene has opened up new opportunities for optoelectronic applications based on this and other low dimensional materials. Recently, population inversion across the Dirac point has been observed directly by time- and angle-resolved photoemission spectroscopy (tr-ARPES), revealing a relaxation time of only ∼130 femtoseconds. This severely limits the applicability of single layer graphene to, for example, Terahertz light amplification. Here we use tr-ARPES to demonstrate long-lived population inversion in bilayer graphene. The effect is attributed to the small band gap found in this compound. We propose a microscopic model for these observations and speculate that an enhancement of both the pump photon energy and the pump fluence may further increase this lifetime.